HUBUNGAN SIMBIOSIS MASYARAKAT ACEH BESAR DENGAN TRADISI HINDU - khairil fazal; Mawardi Mawardi (Prodi Studi Agama-Agama, 2021)
The people of Aceh, which are known as the majority are Muslim, have various customs and traditions and cultures. However, some of the culture and customs of the Acehnese people do not come purely from Islam, but come from Hindu culture, such as Kenduri Blang, Kenduri Laot and Peusijuek culture. Peusijuek is a Hindu culture that has been Islamicized in accordance with Islamic law and has been carried out from generation to generation until now, the Islamization of Hindu culture occurred during the time of Sulthan Ali Mughayat Syah. The symbiotic relationship that occurred between the Acehnese people and the Hindu tradition had occurred thousands of years ago, because before Islam entered Aceh, Hinduism developed earlier in Aceh, so the culture used by the Acehnese at that time was Hindu culture, a symbiotic relationship. This was preceded by trade relations to establishing friendships between nations as well as resulting in cultural contact and inter-ethnic relations, which developed naturally in Aceh at that time. The method in this research is descriptive-qualitative. The data collection technique was carried out through interviews, observation, literature review by reading a number of books related to this research and documentation. The results showed that some of the Blang Bintang community acknowledged that the customs prevailing in Aceh were still influenced by Hindu culture. One of them is the peusijuek culture. The people of Blang Bintang believe that Peusijuek is a Hindu culture that has long developed in Aceh as a legacy from previous ancestors. However, things that are contrary to Islamic teachings have been adjusted after the Islamic Religion came and spread in Aceh.